"The language of flowers" poetics as a code of poetic prose of 19th century (Anna Olenina’s diary and autobiographic prose) - Шарафадина, Клара (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
The article analyses Anna Olenina’s literary experience – the diary and the autobiographical prose – in the context of her use of "the language of flowers" poetics. This code was an original method of poetic prose and everyday landscape graphics at Pushkin's time, accumulating the allegorical plan of the content. The original version of the list of "the language of flowers" is placed in her blog – French etiquette handbook 1811.